The Effectiveness of Stress Management Program on Quality of Life among Methadone Maintenance Treatment Members - s Zarei; z Asadi; kh Zarei (Drug Control Headquarters, Research and Education Office, 2014)
Objective: The aim of present study was to investigate the effectiveness of stress management program on quality of life among methadone maintenance treatment members. Method: In this pre-test, post-test experimental study, 30 individual who referred to Saba MMT center in Pakdasht were randomly divided into experimental group (n=15 participants) and control group (n=15 participants). The experimental group was undergone ten 90 minutes sessions of stress management program and the control group didn't receive any treatment program. Quality of life questionnaire (SF-36) was administered. Result: The results showed that the mean sf-36 score in the experimental group had significant higher increased in comparison of control group. Conclusion: It can be concluded stress management program is effective on increasing of quality of life among methadone maintenance treatment members.